Radiologia Básica (Odontologia), Vinte Anos de Experiência no Ensino Baseado em Problemas Modificado (EPBM) - Watanabe, Plauto Christopher Aranha; Pardini, Luiz Carlos (Revista de Graduação USP, 2017)
Problem-based learning Modified (PBLM) is an innovative approach to the teaching of skills in dentistry. The student theoretical and practical activities (lab) should solve problems about the contents of basic radiology, scriptdriven study-directed, which includes several exercises with questions problem, with individual initiative and finalization in groups. The special feature is the full integration of theoretical and practical activities in a manner inseparable, based on exercises and experiments (scientific research) performed by the students, where the teacher is the tutor, the guardian. Thus, our goal with this article is to bring to the USP community this 20 years experience in the teaching of Basic Radiology, with the EPBM teaching methodology.